Industrialization in Sub-Saharan Africa : Seizing Opportunities in Global Value Chains - Abreha, Kaleb G.; Kassa, Woubet; Lartey, Emmanuel K.K.; Mengistae, Taye A.; Owusu, Solomon; Zeufack, Albert G. (Washington, DC: World Bank, 2021)
Industrialization drives the sustained growth in jobs and productivity that marks the developmental take-off of most developed economies. Yet, academics and policy makers have questioned the role of manufacturing in development for late industrializers, especially in view of rapid advancements in technologies and restructuring of international trade. Concurrently, industrialization and structural transformation are integral to the African Union’s Agenda 2063 and the development strategies of several countries in Sub-Saharan Africa (SSA). Given this renewed interest in industrialization across the region, a central question is not whether SSA countries should pursue industrialization as a potential path to sustainable growth but how to promote the prospects of industrialization. Industrialization in Sub-Saharan Africa: Seizing Opportunities in Global Value Chains addresses this question by reassessing the prospects for industrialization in SSA countries through integration into global value chains. It also examines the role of policy in enhancing these prospects. The main findings indicate that • SSA has not experienced premature deindustrialization; the region has witnessed substantial growth in manufacturing jobs despite a lack of improvement in the contribution of manufacturing value-added to GDP. • The region’s integration into manufacturing global value chains is reasonably high but it is dominated by exports of primary products and engagement in low-skill tasks. • Global value chain integration has led to job growth, and backward integration is associated with more job creation. The report emphasizes the role of policy in maintaining a competitive market environment, promoting productivity growth, and investing in skills development and enabling sectors such as infrastructure and finance. Policy makers can strengthen the global value chain linkages by (1) increasing the value-added content of current exports, (2) upgrading into high-skill tasks, and (3) creating comparative advantages in knowledge-intensive industries.